Stability enhancement in InGaZnO thin-film transistor with a novel Al2O3/HfO2/Al2O3 as gate insulator. (3rd July 2017) - Ding, Xingwei; Qin, Cunping; Xu, Tao; Song, Jiantao; Zhang, Jianhua; Jiang, Xueyin; Zhang, Zhilin
ABSTRACT: This work reports an efficient route for enhancing the stability of amorphous InGaZnO (a-IGZO) thin film transistors (TFTs). It is clearly observed that the off-current in IGZO-TFT decreases by using a novel Al2 O3 /HfO2 /Al2 O3 gate insulator. Temperature-stress measurement were carried out to investigate the stability and the parameters related to activation energy ( EA ) and density-of-states (DOS). The improved electrical properties are attributed to the suppression of leakage current and a lower trapping density at the channel-insulator interface. The results showed that temperature stability and electrical properties enhancements in a-IGZO thin film transistors can probably be ascribed to the smaller DOS.